HIKAYAT ISKANDAR ZULKARNAIN: PENGARUH UNSUR ISLAM DALAM HIKAYAT MELAYU - Lisa Misliani (Kantor Bahasa Lampung, 2017)
AbstractThis paper describes the influence of Islamic elements in the tale of Iskandar Zulkarnain through acomparison of the stories contained in the Qur'an and Malay saga. The focus of this paper is basedon the manuscript numbered Ml. 21 entitled Hikayat Iskandar Zulkarnain edited by Siti ChamamahSoeratno and kept in Kuala Lumpur. The writer tries to show the creativity of the author indeveloping the story and the influence of Islam in the Malay saga. The methodology used by thewriter is literary comparative study of Nusantara.AbstrakTulisan ini mencoba mengangkat pengaruh unsur Islam dalam hikayat Iskandar Zulkarnain melaluisuatu perbandingan kisah yang terkandung dalam Al Qur’an dan hikayat Melayu. Fokus tulisan iniditujukan pada naskah bernomor Ml. 21 yang berjudul Hikayat Iskandar Zulkarnain suntingan SitiChamamah Soeratno dan di disimpan di Kuala Lumpur. Penulis berupaya menunjukkan adanyakreatifitas pengarang dalam mengembangkan cerita dan adanya pengaruh Islam dalam hikayatMelayu. Metodologi yang digunakan penulis adalah kajian sastra bandingan Nusantara.